P194 Upper GI endoscopy is an expensive accessory investigation in the diagnosis of Crohn's disease in children. (16th January 2018) - Al-Araji, R; Muhammed, R
Abstract: Background: ESPGHAN Porto revised criteria recommends upper gastrointestinal endoscopy (OGD) and ileo-colonoscopy with small bowel imaging for all suspected patients with Crohn's disease (CD).OGD is recommended with an aim to improve the diagnostic yield in patients suspected to have Crohn's disease (CD). Aims and Objectives: To analyse the additional diagnostic yield gained from OGD in patients who had diagnostic colonoscopy for suspected IBD. Methods: We have done a retrospective analysis of the data of 100 consecutive CD patients diagnosed in the time period of 2013–2017. All these patients had OGD and colonoscopy. . Endoscopy reports and histology reports were reviewed. We have analysed the cost of OGD in these patients. Results: Out of 100 CD patients (L1 33%, L2 36%, L3 31%) who underwent both OGD and colonoscopy, 52 colonoscopies and 34 OGD were diagnostic macroscopically (Ulcers typical of Crohn's disease were seen). Ileal intubation rate was 80%. Histology was diagnostic of CD in 76% colonoscopies and 41 % of OGDs. Of the 48 patients in whom colonoscopies were non diagnostic macroscopically, only 15 patients (31%) had macroscopic abnormalities of Crohn's disease in OGD. All patients who had diagnostic colonoscopy features of Crohn's disease, histology was confirmative of CD. Of the 48 patients who had non-diagnostic colonoscopy appearance of CD, 33 had diagnostic histology of CD. Only 2 patients had diagnostic histology from OGD out of the 15 patients who had non-diagnostic histology from colonoscopy. In summary OGD provided additional diagnostic yield only in 2% patients (picture 1). Approximately 75 000 euros could have been saved by avoiding OGD in 85% of these patients (average cost of diagnostic OGD is 880 Euros). Conclusions: 85% of children with Crohn's disease can be diagnosed by colonoscopy and histology. OGD provided additional diagnostic yield in only 2% patients with Crohn's disease.